Petrocodon curvitubus, a new species of Gesneriaceae from Guangxi, China - Jin-Xin Wei; Bo Pan; Tao Ding (PhytoKeys)
A new species of Gesneriaceae, Petrocodon curvitubus J.X.Wei, B.Pan & T.Ding, sp. nov. from Guangxi, China, is described and illustrated. The new species is morphologically similar to P. lui and P. tenuitubus, but can be easily distinguished by its elliptic to oblong-ovate leaves, corollas with two purple longitudinal stripes, and conical ovary.